The organic geochemistry of marine-influenced coals. - Sandison, Carolyn M. (Curtin University, 2001)
The importance of organic sulphur fixation in the preservation of organic matter in humic coal-forming environments is demonstrated in this thesis. The transgression of coal depositional systems by marine waters during their deposition and early diagenesis enables the production of reduced inorganic sulphur species by sulphate-reducing bacteria. The presence of these reactive sulphur species, in combination with the altered chemical and microbial regime, influences the preservation and petroleum potential of humic coal.Three lignite samples taken over a two meter depth profile of a core in the Eocene, Heartbreak Ridge lignite deposit, SE Western Australia, were analysed by a suite of geochemical techniques to identify origins and transformation pathways of their organic matter. Rock-Eval, FTIR microscopy, and pyrolysis gas chromatography-mass spectrometry (Py-GCMS) indicate that the composition of the lignite and its extract are typical of immature type III organic matter with a predominance of aromatic and oxygen containing functionalities. Variation in the macromolecular composition of the three lignites are consistent with more pronounced degradation of the organic matter in the lowermost lignite horizon. Nickel boride desulphurisation of polar and asphaltene fractions of the lignites showed the presence of sulphur-bound higher plant triterpenoids, in particular olean-12-ene, n-alkanes of even predominance, C29 steranes and extended 17â(H),21â(H)-hopanes. Deuterium labelling experiments indicated that these components were mostly bound to a single sulphur, at sites about the original functionality in the natural product precursors. The presence of singularly sulphur-bound aromatic ring A degraded and pentacyclic triterpenoids represent the spectrum of aromatic triterpenoid intermediates undergoing diagenesis before sulphur incorporation.Stable carbon isotopic analyses of the free and sulphur-bound aliphatic hydrocarbons confirmed carbon sources from both higher plants and bacteria. Oxygenated lipids consisted of even carbon-numbered n-alkanoic monocarboxylic acids, ù-hydroxy fatty acids and n-alkanols, n-alkan-2-ones, 6,10,14-triinethylpentadecan-2-one, and oxygenated hopanoids and higher plant triterpenoids. BY the onset of sulphurisation in the Heartbreak Ridge lignite, extended hopanoid degradation had come to a hiatus, in marked contrast to the variable alteration of the higher plant triterpenoids. The oxygen-containing lipids of the extracts are implicated as the primary source of the sulphurised hydrocarbons, although not necessarily via direct sulphurisation of their present sent form, but through the formation of more reactive intermediates. These results implicate sulphur fixation as a means by which lipids of similar structures to the natural product precursors are preserved in coal forming environments. That diagenetic alteration of the oxygenated lipids mirrors that of the sulphur-bound hydrocarbons confirms that the onset of marine incursion and the formation of reduced inorganic sulphides does inhibit (and also preserve) the normal biogeochemical transformations of organic matter in coal-forming environments.The technique of reaction gas chromatography-mass spectrometry (R-GCMS) was also applied to the analysis of the polar extracts from a Heartbreak Ridge lignite, together with the polar extracts from the Monterey Formation shale (Naples Beach, USA; Miocene age). Palladium black acting as a catalyst under hydrogen carrier gas in the vaporising injection port of a GCMS, effected gas phase reaction of the volatile constituents in the polar mixtures.The fully active catalyst effected hydrogenation, desulphurisation and decarbonylation/decarboxylation reactions. Polar fractions of the Heartbreak Ridge lignite reacted to produce angiosperm-derived triterpenoids and bacterially-derived hopanoids. The reaction of the Monterey Formation shale polars resulted in the formation of high relative amounts of pristane and phytane with a predominance of the latter, as well. as a suite of steroidal and triterpenoid moieties, typical of marine organic matter. However, R-GCMS provided less detailed information on the exact nature of the functionalised lipids partitioned within the polar fraction than that obtained by more conventional wet chemical analyses.The compositions of 35 marine-influenced, bituminous coals, from the Eocene Brunner Coal Measures of New Zealand were studied to assess the effect of the timing of marine incursion on the molecular characteristics of coals. Based upon their stratigraphic position and their volatile matter and total sulphur contents, coal samples were classified into those where the mire was flooded during or at the end of deposition (Class A/B) and those that experienced postdepositional access of marine water during later diagenetic stages (Class C/D). Rock-Eval pyrolyses showed that sulphur-rich Brunner coals generally display moderate increases in pyrolytic yields with respect to the low-sulphur Brunner coals. Class A-C coals generally release larger quantities of hydrocarbons during Rock-Eval pyrolysis than the Class D coals, suggesting that sulphur fixation can enhance the hydrocarbon potential of buried mires, provided sulphur is introduced early. Variation in Carbon Preference Indices, isoprenoid/alkane ratios, the Methylphenanthrene Index and phenanthrene/anthracene of bitumens and pyrolysates both within different seam profiles and between different sampling localities can be attributed to changes in microbial regime as well as subtle variations in rank.Pristane/phytane, dibenzothiophene/phenanthrene and thiophene ratios are closely related to organic sulphur contents, but are also influenced by these changes in rank and differences in the timing of marine incursion.Organic sulphur contents and biomarker compositions are related through a drillcore profile, which confirms the role of diagenetic sulphur sequestration in preserving specific biomarkers (steranes, higher plant triterpanes, extended hopanes) in coal-forming environments. Biomarker ratios that vary accordingly include the homohopane index, Ts/Tm, C29Ts/norhopane, C30 diahopane/hopane, sterane/hopane ratio, C29 diasterane/sterane, oleanane/hopane, oleanoid triterpane/hopane, and ring A degraded triterpanes/des-E-hopane.Diasterane concentrations were greatest in high sulphur coals. It is suggested that sterenes, generated from sulphur-bound steroids of regular stereochemistry in the subsurface, undergo acid-catalysed rearrangement and hydrogenation to enhance diasterane concentrations. A similar formation mechanism can be invoked for the rearranged hopanes (Ts, C29Ts, C30 diahopane) and oleanoid triterpanes. The timing of sulphur fixation does not appear to have influenced the formation of biomarkers except in one case. The only lipid class that degraded rapidly enough for the precursors required for sulphurisation to be removed prior to saline access is the higher plant triterpenoids. Stable carbon isotopic analysis of the n-alkanes, isoprenoids and hopanoids from the Pike River Outcrop seam section confirms both higher plant and microbial sources. In particular, the carbon isotopic composition of phytane suggests that methanogenic decomposition of the Pike River peat occurred. The isotopic signatures are invariant to changes in the degree or timing (Class A-C only) of sulphur access to this outcrop.This body of work finds that the introduction of marine waters (and the formation of reduced sulphides) in the early stages of mire and peat development preserves the inherited lipid composition of the peat and does not overwhelm this biotic signature during sulphate reduction. As such, the selective preservation of certain biomarkers enables their use as indicators of marine-influence in source rocks. The application of several biomarker ratios to the characterisation of crude oils from the Taranaki Basin of New Zealand provides further evidence for the generation of liquid hydrocarbons from marine-influenced, angiosperm-rich coals.